PROGRAM PUSAKA SAKINAH BAGI CALON PENGANTIN MUALLAF: STUDI KASUS KUA KECAMATAN SINGKIL - Khairuddin, Khairuddin; Sapridanur, Risky (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Pusaka Sakinah is a program of the Ministry of Religious Affairs that aims to minimize divorce in Indonesia. This program is successful, but there are still families that are not harmonious and even end in divorce. The purpose of this study is to analyze the implementation of the pusaka sakinah program on muallaf brides-to-be at the Singkil KUA. This research is empirical research that collects data through observation and interviews. This research shows that the implementation of the Sakinah Heritage Program at the Singkil Religious Affairs Office, Aceh Singkil Regency is still ongoing. For prospective brides, especially prospective brides who have converted to Islam, more requirements need to be given, in order to create a marriage that is sakinah mawaddah and warahmah. There are several factors that support the implementation of the pusaka program at the KUA of Singkil Regency, namely government policy, infrastructure, competence of facilitators and participants, and inhibiting factors, namely the absence of regulations requiring participation in the Pusaka Sakinah program, the enthusiasm of the community to participate in the Pusaka Sakinah program is not fully optimal.